(untitled) (Journal of the College of Education for Women, 2018)
This research provides a new method to study praise poetry that can be used as a course to teach English and Arabic to students in the College of Education. This research answers two questions: Is it possible to examine praise poetry as a tagmeme? Is this analysis of great help in teaching English and Arabic to students in the College of Education? The data that will be chosen for the purpose of analysis are two of Shakespeare’s sonnets and two of AL Mulik’s poems. The sonnets selected for this purpose are 17 and 18. AL Mulik’s poems selected for the same purpose are 8 and 9. Each line in both English and Arabic data is numbered by the researcher herself. Then, those lines are grouped into sentences to facilitate the process of analysis. The researcher has relied on Pike and Pike (1977) model for the analysis. The study has reached that AL Mulik’s poems and the sonnets are considered as tagmeme and that there is a connection between a AL Mulik’s poems and the sonnets. The analysis conducted in this research can be of great help to teach students learning English and Arabic in the College of Education because it supplies them with a novice method of studying the texts to be learned.